Asynchronous Online Discussion Forums: Effective Undergraduate and Graduate Course Approaches - Eric J. Robbins; James F. Fairbank (Park University, 2023)
Asynchronous online discussion (AOD) can provide an interactive educational experience through formation of learning communities that enable students to develop professional knowledge and critical thinking skills as they engage with colleagues and instructors. We find significant differences between undergraduate and graduate student perceptions of the efficacy of AOD. In this paper, we explore the pedagogical benefits of AOD and describe considerations that guide how they are designed and managed effectively and efficiently. Additionally, we report the results of a survey that measures student perceptions of the extent to which AOD provided a positive educational experience and contributed to their learning.